2020
DOI: 10.3389/fnhum.2020.602360
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Common Aspects of Obesity and Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is an example of age-related dementia, and there are still no known preventive or curative measures for this disease. Obesity and associated metabolic changes are widely accepted as risk factors of age-related cognitive decline. Insulin is the prime mediator of metabolic homeostasis, which is impaired in obesity, and this impairment potentiates amyloid-β (Aβ) accumulation and the formation of neurofibrillary tangles (NFTs). Obesity is also linked with functional and morphological alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 172 publications
0
15
1
Order By: Relevance
“…These particular features are associated with chronic inflammation, increased oxidative stress, and impairment in insulin signaling and energy metabolism [23,24]. Additionally, due to the potential multifactorial role of obesity in pathological processes seen in AD, obesity could serve as a risk factor for this disease [25]. Of note, patients with T2DM have a 2-fold higher risk of developing AD than healthy subjects [26].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…These particular features are associated with chronic inflammation, increased oxidative stress, and impairment in insulin signaling and energy metabolism [23,24]. Additionally, due to the potential multifactorial role of obesity in pathological processes seen in AD, obesity could serve as a risk factor for this disease [25]. Of note, patients with T2DM have a 2-fold higher risk of developing AD than healthy subjects [26].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…An increasing amount of data suggests that adipose tissue-associated inflammation is the primary mechanism by which obesity becomes a risk factor for developing cognitive disorders, especially AD [25,84]. The presence of an adiposity-related inflammatory microenvironment leads to the formation of inflammasome complexes that may amplify innate immune response not only locally in adipose tissue but also in the whole organism, making it systemic [85,86].…”
Section: Adiposity-related Inflammationmentioning
confidence: 99%
“…The inflammation induced by the dysregulation of peripheral lipid metabolism links obesity and its complications with AD [ 56 , 89 , 136 ]. Researchers have demonstrated that inflammatory challenges in the periphery trigger neuroinflammation [ 87 ], which can then contribute to the pathogenesis of AD in several ways, including interacting with Aβ metabolism [ 88 , 137 139 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral IR is associated with dysregulated lipid metabolism, resulting in the overload of FFAs and the activation of cytokines in the periphery. Excessive levels of peripheral cytokines can cross and damage the BBB, leading to neuroinflammation and therefore inducing brain IR [ 89 ]. This mechanism has been supported by several experiments with rodent models that demonstrated that chronic peripheral IR may lead to brain IR as well as brain dysfunction [ 149 , 150 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis suggested that sarcopenia is associated with cognitive dysfunction [ 4 ]. The correlation between obesity and cognitive dysfunction has been shown in several investigations [ 5 , 6 ]. Exacerbated insulin resistance [ 7 ], energy metabolism dysregulation [ 8 ], and increased oxidative stress and neuroinflammation [ 9 ] have been proposed as potential causal factors.…”
Section: Introductionmentioning
confidence: 99%